Trends and current situation in the diffusion and utilization of information technology. - SOUBRA, Yehia (1993)
Classifies and enumerates the different elements that are included in the definition of IT and telecommunications. Notes that these elements should be seen in a dynamic context due to rapid developments in microelectronics. Discusses the diffusion and utilization of IT in both developed and developing countries, and concludes that this discussion has helped to highlight the issues facing countries at different stages of development.